Family support and anxiety: A correlational study among women with stage III breast cancer - Narsiti, Narsiti; Handian, Feriana Ira; Firdaus, Achmad Dafir (Palembang MediRose Publisher, 2023)
Background: Breast cancer exerts a broad impact on psychological well-being, notably leading to heightened anxiety levels. Uncontrolled anxiety can interfere with planned therapy, making it crucial to understand its underlying factors. Objective: This study aims to investigate the relationship between family support and anxiety in patients with stage III breast cancer. Methods: The study employed a cross-sectional design and selected 41 respondents through purposive sampling. Family support was assessed using the Sarason Social Support Questionnaire, while anxiety levels were measured with The State-Trait Anxiety Inventory (STAI). Statistical analysis utilized the Spearman-Rho correlation. Results: The majority of breast cancer patients in the sample exhibited low levels of family support (n=22, 53.7%). On average, respondents reported an anxiety score of 80.78. The analysis demonstrated a significant relationship between family support and anxiety in breast cancer patients (p = 0.04), with a correlation coefficient of -0.316. Conclusions: These findings emphasize the importance of enhancing the quality of service in the treatment room and initiating early detection of patients experiencing psychosocial issues. Additionally, involving families in the therapy implementation process may prove beneficial. Nurses play a crucial role in addressing these aspects to better support patients throughout their breast cancer journey.